Transformation of teachers' teaching documentations with innovative and interactive quick response codes (INTEGRATED (Journal of Information Technology and Vocational Education), 2024)
The integration of technology into pedagogical practices has revolutionized teaching and learning methodologies. Quick Response (QR) codes, a ubiquitous form of two-dimensional barcodes, have emerged as a promising tool to enhance teaching documentations. This qualitative study delves into the transformation of teachers' teaching documentations through the implementation of innovative and interactive QR codes. Employing a case study approach, the research explores the experiences and perspectives of teachers who integrated QR codes into their lesson plans, worksheets, and other teaching materials. Data collection methods encompass semi-structured interviews, classroom observations, and document analysis. The findings reveal that QR codes have significantly transformed teachers' teaching documentations by fostering interactive and engaging learning experiences. Teachers perceived QR codes as valuable tools for promoting student engagement, enriching content delivery, and facilitating differentiated instruction. However, challenges related to technical accessibility, teacher training, and curriculum integration emerged as potential barriers to widespread adoption. The study concludes by emphasizing the transformative potential of QR codes in enhancing teaching documentations and offers recommendations for effective implementation.